Pengaruh Media Sosial terhadap Karakter Siswa di SMA Katolik Lembean - Paulus Joseph Mentang; Shefry Yanny Fransisco Topit (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
The purpose of this study was to analyze the effect of social media on the character of students at SMA Don Bosco Lembean Catholic High School. Primary data was obtained through a questionnaire distributed to 128 students. There are 3 hypotheses. Two hypotheses are descriptive hypotheses and 1 hypothesis is tested by simple linear regression analysis. The results of the study concluded that the 3 hypotheses proved to be strong and significant. This finding indicates that social media greatly influences the character of Don Bosco Lembean Catholic High School students. Social media plays a very important role in the formation of student character. Positive or negative influences are largely determined by the assistance of teachers and parents at home. This finding is also an input for foundations and teachers to really pay attention to the use of social media from students both at school and outside of school.